Operation Strategy of Continuous Gravity Measurement as Complementary to Seismic Survey on Geological CO2 Storage - Masao SORAI; Hiroki GOTO; Mitsuhiko SUGIHARA; Yuji NISHI; Shinsuke NAKAO (Journal of MMIJ, 2021)
Toward the implementation of geological CO2 storage, cost reduction of CO2 monitoring during and after injection into targeted reservoirs is the key issue. The continuous gravity measurement using a superconducting gravimeter, which has been applied to the demonstration project site in Japan ahead of the rest of the world, has a potential to resolve the issue from the viewpoint of a complement to the high-cost seismic survey. The concept is such that the continuous gravity measurement is substituted for constant monitoring and that the use of seismic survey could be limited only when any anomaly is detected. The comparison of the monitoring cost after the completion of CO2 injection indicated that applying gravity measurement can reduce costs by up to 15 to 50% of the seismic cost. The current detection limit of gravity change is around 1 μGal based on the application result in the coastal area in Japan. However, the time series analysis using pseudo gravity data suggested the possibility of anomaly detection even below the detection limit. Further improvement of analysis precision would lead not only to more rapid and more reliable anomaly detection but also to contribution to the cost reduction during the CO2 injection period.